(3Gdbhd GdHOjY aj GdUdGI Ydi GdMHjH GdTajYs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3jhSa Hf CHj HcQ GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa bOQ SjOfG eMeO GdfHi GdcQje s
(3BNQgG (B:s
(3hGddg GdeSJYGf hYdjg GdJcdGf hGdGdgGe dcKQI GdUdGI Ydi fHjfG Ydjg GaVd GdUdGI hGdSdGe BNQ cJGH Gdbhd GdHOjY ai GdUdGI s
(3HgG fXGe GdJYbjHIs
(3gPg GdfSNI efbhdI Yf fSNI HNW GdeUfa cGf aQZ efgG SfI (B860 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
Keywords: (3GdCOHs